2003
DOI: 10.1007/s00134-003-1858-0
|View full text |Cite
|
Sign up to set email alerts
|

Critical illness polyneuromyopathy: the electrophysiological components of a complex entity

Abstract: Electrophysiological and histological examinations showed significant overlapping of several pathogenic components of neuromuscular involvement in critically ill patients, namely decreased muscle excitability, myopathy, axonal motor neuropathy and sensory neuropathy. The characterisation of the electrophysiological components of a complex polyneuromyopathy is preferred to the strict categorisation of abnormalities into critical illness myopathy and polyneuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
1
35

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(165 citation statements)
references
References 32 publications
3
126
1
35
Order By: Relevance
“…A clear correlation between motor electrophysiology and histopathological abnormalities could not be demonstrated in all studies [28,29]. Morphological changes in CIP can be seen in nerve biopsies e.g.…”
Section: Diagnostic Featuresmentioning
confidence: 84%
See 1 more Smart Citation
“…A clear correlation between motor electrophysiology and histopathological abnormalities could not be demonstrated in all studies [28,29]. Morphological changes in CIP can be seen in nerve biopsies e.g.…”
Section: Diagnostic Featuresmentioning
confidence: 84%
“…CIP and CIM may coexist and their relative contribution to the weakness may vary [24]. Thus, many clinicians suggest to consider it as a complex entity of polyneuromyopathy [29]. Recognizing CIP or CIM often improves management, although no specific pharmacologic treatments are known at present [91].…”
Section: Conclusive Remarksmentioning
confidence: 99%
“…It was later suggested that neuropathy and myopathy might be acquired in tandem during critical illness [17]. Multiple prospective studies subsequently reported combined myopathic and neuropathic findings in individual patients on the basis of either electrophysiologic or biopsy specimens [12,18,19]. Data allowing for specific classification of NMD revealed similar proportions of patients diagnosed with CIM (49/144, 34%), CIP (51/144, 35%), and combined CIM/CIP (44/144, 30.6%) [7].…”
Section: Incidence Of Acquired Neuromuscular Dysfunction In the Icumentioning
confidence: 99%
“…However, recently it has been recognized that the two syndromes often coexist [9,18,19,62]. CIP and CIM could occur together either because they are distinct syndromes that are due to coexisting risk factors or because they represent different manifestations of a single underlying disorder.…”
Section: Inexcitability Of Sd Muscle Is Due To Abnormal Regulation Ofmentioning
confidence: 99%
“…Therefore, it is difficult to accurately determine the incidence rates of CIP and CIM [12,16,17]. Intriguingly, recent data suggest that CIP and CIM frequently coexist, a condition that has been termed CINM [18]. The pathophysiology of CINM/ICUAW is complex and includes the sequelae of bed rest, the effects of critical illness-induced cytokine production, and possibly the interplay of drugs, such as neuromuscular blocking agents and corticosteroids (Figure 1).…”
Section: Introductionmentioning
confidence: 99%